2016
DOI: 10.1002/berj.3255
|View full text |Cite
|
Sign up to set email alerts
|

Classroom disciplinary climate in secondary schools in England: What is the real picture?

Abstract: This paper uses international data from a range of sources, principally the 2013 round of the Teaching and Learning International Survey (TALIS 2013), to provide new information on classroom disciplinary climate in secondary schools in England. The paper advances the literature in three distinct ways. Firstly, the data show that teachers in England perceive that there is considerable disruption in their classrooms. While some reports, especially from official sources, have suggested that classroom disruption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
1
9
0
2
Order By: Relevance
“…In particular, the results for the tree in terminal node 8 indicated that it can correctly predict 94% of high performers based on whether they have more positive epistemic beliefs about science (>−0.12), more learning time (>1.58), and more positive science self‐efficacy (>−1.05), whereas the results for terminal node 1 indicated that it can correctly predict 92% of low performers based on whether they have less positive epistemic beliefs (<−0.12) and less learning time (<3.17). Some studies have indicated that the influence of instructional quality is generally associated with students' motivation, satisfaction, academic outcomes (Arum & Velez, ; Jenkins & Ueno, ), and self‐efficacy (Cheema & Kitsantas, ). Other studies have suggested that students' characteristics (Kirschner, Sweller, & Clark, ) and classroom or school environments (Creemers & Kyriakides, ) impact the effectiveness of inquiry‐based activities.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the results for the tree in terminal node 8 indicated that it can correctly predict 94% of high performers based on whether they have more positive epistemic beliefs about science (>−0.12), more learning time (>1.58), and more positive science self‐efficacy (>−1.05), whereas the results for terminal node 1 indicated that it can correctly predict 92% of low performers based on whether they have less positive epistemic beliefs (<−0.12) and less learning time (<3.17). Some studies have indicated that the influence of instructional quality is generally associated with students' motivation, satisfaction, academic outcomes (Arum & Velez, ; Jenkins & Ueno, ), and self‐efficacy (Cheema & Kitsantas, ). Other studies have suggested that students' characteristics (Kirschner, Sweller, & Clark, ) and classroom or school environments (Creemers & Kyriakides, ) impact the effectiveness of inquiry‐based activities.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers complain of inadequate training to manage socio-emotional difficulties and challenging behaviour, and these difficulties are associated with higher stress levels, poorer mental health, burnout, and exit from the profession (Webster-Stratton et al , 2001 ; Jennings and Greenberg, 2009 ). Disruption in the classroom can undermine the quality of teaching and interrupt the learning of all the children in the class (Jenkins and Ueno, 2017 ). An intervention that supports teachers to optimise children's mental health and behaviour might benefit every child subsequently taught by that teacher as well as the teacher themselves, and might be substantially more cost-effective than direct work with successive cohorts of children.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption in the classroom can undermine the quality of teaching and interrupt the learning of all children in a class. 1 Conduct disorder (or behaviour that consistently violates social norms to the extent that a child's ability to function is impaired) is the most common childhood mental health problem, with a prevalence of 5-6% in the UK and high levels of comorbidity. 2,3 Furthermore, levels of disruptive behaviours are normally distributed throughout the population.…”
Section: Disruption In Schoolmentioning
confidence: 99%